In vivo evaluation od disintegration of four different ortjodontic band cements - Saad, Bashir M. (My University, 2003)
IN VIVO EVALUATION OF DISINTEGRATIOIN OF FOUR ORTHODONTIC BAND CEMENTS NAME: Bashir M . Saad SUPERVISOR: Assistant Prof . Dr Toros Alcan DATE OF PRESENTATION: 22/ 05/ 2003 DEPARTEMENT: Orthodontic

The aim of this study was to evaluate the 3 months in vivo disintegration rate of 4 different types of luting cement, multi cure glass ionomer orthodontic band cement (3M unitek. Monrovia. USA), composite resin (ultra band-lok - Reliance ortho product), transbond plus light cure band adhesive (3M unitek), and MR lock LC visible light cure band cement (American orthodontics). Head gear tubes measuring (1.2 mm in diameter and 3 mm in length )were filled with the cements ( one cement for each tube ) the tubes were placed on the four first molar orthodontic bands . Nine patients, 6 females and 3 males with a mean age of 15.6 years, were selected for this study. All patients had fully erupted and non caries permanent first molars. Although, two of the tested cement (multi cure glass ionomer cement and MR LOCK LC) showed variable amount of vertical cement loss and the other two tested cements (ultra band lok and transbond plus) showed variable amount of swelling, Analysis of the disintegration rate with one-way ANOVA test demonstrated no significant difference existing between the tested cements. Also application of paired t test to determine the effect of the location on the disintegration rate was not significance. ÖZET YAPIŞTIRICI SİMANLARIN İN VİVO ORTAMDA ÇÖZÜNMELERİ Bu çalışmanın amacı 4 farklı tip yapıştırıcı simanın ; multi cure cam iyonomer ortodontik bant simanı (3M Unitek, Monrovia, USA), kompozit rezin (ultra band-lok-Reliance ortho product), transbond plus light cure bant yapıştırıcısı (3M unitek) ve MR lock LC görülür ışıkla sertleşen bant yapıştırıcısı (American Orthodontics), in vivo olarak 3 aylık çözünme hızlarının değerlendirilmesidir. Head gear tüpleri (1.2mm çapında ve 3mm uzunluğunda) yapıştırıcı siman ile doldurulmuş (her tüpe bir siman), tüpler dört birinci molar dişlerindeki ortodontik bantlara yerleştirilmiştir. Bu çalışma için 6 bayan 3 erkek, yaş ortalaması 15,6 olan 9 hasta seçilmiştir. Tüm hastaların daimi birinci molar dişleri tamamen sürmüştür ve çürüksüzdür. Test edilen iki yapıştırıcı (multi cure cam iyonomer siman ve MR LOCK LC) değişik miktarda dikey siman kaybı göstermiş olmakla birlikte ve diğer iki test edilen siman (ultra band lok ve transbond plus) değişik miktarlarda şişme göstermiş olmakla birlikte çözülme hızlarının tek yönlü ANOVA testi analiz sonuçları test edilmiş simanlar arasında belirgin fark göstermemektedir. Ayrıca lokalizasyonun çözülme üzerindeki etkisini belirlemek için uygulanan paired t testi sonuçları anlamlı deği
Keywords: Diş Hekimliği; Ortodonti